Shared and Distinct Fractional Amplitude of Low-Frequency Fluctuation Patterns in Major Depressive Disorders With and Without Gastrointestinal Symptoms - Fu, Xiaoya; Li, Huabing; Yan, Meiqi; Chen, Jindong; Liu, Feng; Zhao, Jingping; Guo, Wenbin (Frontiers in Psychiatry, 2021)
Objective: Gastrointestinal (GI) symptoms are fairly common somatic symptoms in depressed patients. The purpose of this study is to explore the influence of concomitant GI symptoms on fractional amplitude of low-frequency fluctuation (fALFF) patterns in patients with major depressive disorders (MDD) and investigate the connection between aberrant fALFF and clinical characteristics. Methods: This study included 35 MDD patients with GI symptoms (GI-MDD patients), 17 MDD patients without GI symptoms (nGI-MDD patients) and 28 healthy controls (HCs). The fALFF method was used to analyze the resting state functional magnetic resonance imaging data. The correlation analysis and pattern classification were employed to investigate the relationship of fALFF pattern with clinical characteristics in the patients. Results: GI-MDD patients exhibited higher scores in HRSD-17 scores and suffered more severe insomnia, anxiety/somatization and weight loss than nGI-MDD patients. GI-MDD patients showed higher fALFF in the right superior frontal gyrus (SFG)/middle frontal gyrus (MFG) and lower fALFF in the left superior medial prefrontal cortex (MPFC) compared with nGI-MDD patients. A combination of the fALFF values of these two clusters could be applied to discriminate GI-MDD patients from nGI-MDD patients with an accuracy, a sensitivity and a specificity of 86.54%, 94.29% and 70.59%, respectively. Conclusion: GI-MDD patients showed more severe depressive symptoms. Increased fALFF in the right SFG/MFG and decreased fALFF in the left superior MPFC might be distinctive neurobiological features of MDD patients with GI symptoms.